Newman and Carranza's clinical periodontology and implantology - Newman, Michael G.; Klokkevold, Perry R.; Elangovan, Satheesh; Hernandez-Kapila, Yvonne L.; Carranza, Fermin A.; Takei, Henry H. (St. Louis, MO : Elsevier, 2024)
Learn and master a range of clinical techniques and achieve therapeutic goals with Newman and Carranza's Clinical Periodontology and Implantology, 14th Edition! Unmatched for its comprehensive approach, this resource provides detailed, up-to-date information on the etiology and pathogenesis of periodontal disease. Basic and advanced evidence-based information on the various treatment modalities employed in periodontics and implantology is presented in an easy-to-read format, with callout boxes throughout the text highlighting the clinical relevance of foundational basic science information. Full-color photos and radiographic images depict periodontal conditions and procedures, and the Atlas of Periodontal Pathology is one of the most comprehensive ever compiled in a periodontal textbook. Written by a team of leading experts led by Michael G. Newman, this text not only demonstrates how to perform periodontal procedures but explains the evidence supporting each treatment and provides knowledge on how to achieve the best possible outcomes of periodontal therapy and implant treatment. An eBook version is included with print purchase, providing access to all the text, figures, and references, plus the ability to search, customize content, make notes and highlights, and have content read aloud. The eBook version included with print purchase also includes Periopixel 3D color illustrations, a periodontal classification calculator and interactive learning tool, review questions, case studies, videos, 3D animations, and more! This edition features new chapters on Precision Medicine, Pocket Reduction Therapy, Periodontal Referral, and Digital Implant Workflows, as well as an updated glossary of terms linked to the eBook. It also features first-of-its-kind content on the effects of COVID-19 on treatment from key opinion leaders in this area. Case studies reflect the new format of the Integrated National Board Dental Exam (INBDE).
Fundamentals and Essential Evidence -- Etiology and Pathogenesis -- Gingival Pathology -- Periodontal Pathology -- Conditions Affecting the Periodontal Patient -- Occlusion -- Levels of Clinical Significance -- Surgical Management of Periodontal Conditions -- Fundamentals of Implantology -- Prosthetic Considerations -- Surgical Procedures -- Digital Implant Workflow -- Complications, Supportive Care and Results of Implant Treatment.
Previous edition published as: Newman and Carranza's clinical periodontology / [edited by] Michael G. Newman, Henry H. Takei, Perry R. Klokkevold, Fermin A Carranza. Thirteenth edition. Philadelphia, PA : Elsevier, [2019].
Includes bibliographical references.
Keywords: Periodontics; Oral Surgical Procedures